Economic impacts of the RES Obligations in Austria - an Application of the Macro-Econometric Model e3.at - Ulrike Lehr; Marc Ingo Wolter; Anett Großmann (Gesellschaft für Wirtschaftliche Strukturforschung (GWS), 2009)
The year 2008 started in January (Jan 23, 2008) with ambitious European initiatives on climate change when the European Commission suggested a climate packages with new targets for energy from renewable sources (RES), for the design of the third phase of the emission trading system, for a directive on carbon capture and storage systems (CCS), for the fuel directive, and a directive on CO2 limit for new vehicles. Several of these proposed directives have been an issue of fierce discussion during the year, especially as the extent of the financial crisis gradually came to the fore and the fears of a worldwide economic crisis grew. At the end of 2008, however, the package passed the European parliament (Dec. 17, 2008) though several concessions had to be made concerning the emission trading system or the vehicle directive. However, seemingly unaffected by current fears and therefore largely unaltered the directive of the European Parliament and of the Council on the promotion of the use of energy from renewable sources in Europe passed with a rather high amount of yes votes of the whole package, indicating that the support for energy from renewable sources still seems strong. The Directive establishes a common framework for the promotion of energy from renewable sources. It sets mandatory national targets for the overall share of energy from renewable sources in gross final consumption of energy and for the share of energy from renewable sources in transport. (COM(2008)0019 - C6-0046/2008 - 2008/0016(COD) The national overall targets are set individually for each country and the required increases compared to 2005 are as low as 22% (Sweden, Latvia) or as high as more than 1000% in the case of the UK (c.f. full table in the Appendix). Each country will have to develop a strategy for a sustainable pathway to reach the target. Though the strategic decisions will be on the national levels for each country, the knowledge of the targets for the European Community provides useful information to back the decision. Domestic support of RES technologies can induce a lead market and create international export opportunities. Observing the strategies of the other EC member states will affect the choice of the national efficient and effective policy mix. Austria is an interesting case study insofar as it already uses renewable energy to a large extent (23.3% in 2005) and still has to increase it by almost 50% to 34% by 2020. This increase will come with large necessary investments and will require a combined energyefficiency strategy. To answer the question how and at what overall economic costs in terms of GDP and employment effects the targets can be reached a scenario has to be developed and tested with the help of a model that reflects the economic and environmental interdependences. Therefore, to analyze the overall effects a highly interdependent resource economic modeling approach is needed. The macro-econometric model e3.at has been developed to answer such questions. The article is organized as following. Section 2 describes the model e3.at. Section 3 suggests an energy-efficiency scenario that meets the ECs targets. Section 4 presents modeling results and section 5 concludes.
Keywords: C51; C52; C53; E17; 330; Austria; Macro-Econometric Model; e3.at; Economic impacts; RES Obligations